DETECTION OF BONE MARROW EDEMA IN VERTEBRAL COMPRESSION FRACTURES USING THIRD-GENERATION DUAL-ENERGY COMPUTED TOMOGRAPHY AND VIRTUAL NONCALCIUM TECHNIQUES - TAPAS KUMAR SAHU; JEEVITHAN SHANMUGAM; GEETHANJALI SUNDARAM; SEETHARAMAN CANNANE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Vertebral compression fractures (VCFs) are a significant clinical concern worldwide, often resulting in increased morbidity and mortality. Malignancies, secondary osteoporosis, post-menopausal osteoporosis, and trauma are the most common causes of this. Early detection and appropriate treatment are crucial to alleviate pain, initiate therapy, prevent complications, and reduce the risk of new fractures. Various imaging modalities, including magnetic resonance imaging (MRI) and computed tomography (CT), are used to diagnose VCFs. However, MRI has limitations, and CT advancements, particularly dual-energy CT (DECT) with virtual non-calcium (VNCa) imaging, offer the best alternatives for detecting bone marrow edema. Methods: This observational study was conducted at Kovai Medical Center and Hospital, Coimbatore, involving 46 adult patients with detectable VCFs. Approval was obtained from the Institutional Ethical and Scientific Committee, and informed consent was received from all participants. Patients underwent spine MRI and DECT on the same day. MRI was performed using Siemens 3T Skyra or Philips Ingenia 1.5T scanners, and DECT scans were taken using a third-generation 192-slice dual-source CT scanner. DECT images were processed to create VNCa images. Image analysis was conducted blindly, with MRI images showing increased STIR signal intensity and decreased T1 signal considered positive for bone marrow edema. DECT images were evaluated for edema presence. Results: The study participants had a mean age of 58.65±15.47 years, with 54.3% females and 45.7% males. A total of 84 fractures were detected across 782 vertebral bodies, with 57.14% acute and 42.86% chronic. Fractures were evenly distributed between the dorsal (57.14%) and lumbar (42.86%) levels, predominantly at the dorsolumbar junction. Using the Genant grading system, fractures were classified into grades 0–3, with most fractures being grade 1 (35.7%) and grade 3 (35.7%). DECT demonstrated high diagnostic performance, with a sensitivity of 87.50%, specificity of 91.66%, positive predictive value of 93.33%, negative predictive value of 84.62%, and overall accuracy of 89.29%. The positive and negative likelihood ratios were 10.50–0.14, respectively. Discussion: The study confirms that third-generation DECT with VNCa imaging is highly effective in detecting bone marrow edema in VCFs, showing diagnostic accuracy comparable to MRI. Previous studies corroborate these findings, indicating that DECT can serve as a reliable alternative, especially for patients with MRI contraindications. The advancements in DECT technology enhance its ability to differentiate and visualize bone marrow abnormalities, making it a valuable diagnostic tool in clinical practice.